Epidemiology and Demographic Profile of Inflammatory Bowel Disease in Nepal - Ranjan, Mukesh K; Pathak , Rahul (Journal of Institute of Medicine Nepal, 2023)
Inflammatory bowel disease (IBD) is a chronic disease of the gastrointestinal tract. Once thought to be a disease of the developed nations, the burden of IBD has been rising in Asian countries. Inflammatory bowel disease leads to severe impairment in the quality of life of the patients. There have been numerous studies across the globe which have provided new insight into different aspects of this disease. Not only IBD is being diagnosed more but patients are also becoming more aware of this debilitating condition. It is encouraging to see a few studies from Nepal in the recent past. However, the epidemiological and demographic features of IBD remain largely unknown. Through this review, we aim to gain insight into the epidemiology and demographic features of patients with IBD in Nepal.